Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru - Arinda Frismelly; M. Giatman; Ernawati (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2021)
The style or manner of a principal in his capacity as a leader will determine the success of improving the performance of teachers under his leadership. The purpose of this study was to obtain data on the principal's leadership style in improving teacher performance. Through a qualitative approach with descriptive methods, data collection techniques were carried out through a literature review consisting of 6 relevant articles regarding the influence of leadership style on teacher performance. The results found applying an instructive leadership style (telling) in improving discipline, (2) principals applying a consultative leadership style (selling) in increasing teacher work motivation, (3) principals applying a delegating leadership style (delegating) in increasing teacher responsibility, and the authoritarian leadership style is one of the leadership styles that is implied in order to improve teacher discipline so as to produce good performance and increase the teacher's sense of responsibility in learning. It is recommended that the principal can apply a better or varied leadership style so that the desired goals can be achieved properly and maximally.